2005
DOI: 10.1139/z05-109
|View full text |Cite
|
Sign up to set email alerts
|

Size-related performance variation in the wood frog (Rana sylvatica) tadpole tactile-stimulated startle response

Abstract: I described the initial response of the Rana sylvatica LeConte, 1825 tadpole to predator contact, that is, the tactile-stimulated startle response (TSR). Because tadpole survival from predation increases with tadpole size and with exposure to chemical predator cues during development, I anticipated that TSR performance would vary accordingly among tadpoles. Startle responses were stimulated in a laboratory setting and filmed using high-speed video. This method allowed analysis of performance at fine spatial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 50 publications
1
14
1
Order By: Relevance
“…However, in many cases, the orientation at the end of stage II was different from the original. In a previous study encompassing a broader size range of wood frog tadpoles, I showed a similar pattern: the average rotation of wood frog head/body during stage I was 1301 and, during stage II, rotation averaged 1131, almost reversing stage I rotation (Eidietis, 2005). The median head/body orientation at the end of stage II was very close to the original orientation (Fig.…”
Section: Kinematicssupporting
confidence: 68%
See 2 more Smart Citations
“…However, in many cases, the orientation at the end of stage II was different from the original. In a previous study encompassing a broader size range of wood frog tadpoles, I showed a similar pattern: the average rotation of wood frog head/body during stage I was 1301 and, during stage II, rotation averaged 1131, almost reversing stage I rotation (Eidietis, 2005). The median head/body orientation at the end of stage II was very close to the original orientation (Fig.…”
Section: Kinematicssupporting
confidence: 68%
“…As noted above, researchers report that the first two stages of the tadpole TSR include short, time-dependent peaks in linear acceleration of the head/body (Hoff, '88;Wilson and Franklin, '99, 2000;Eidietis, 2005). Similar time dependence of rotational acceleration has not yet been described.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Taken together, their positive association with body size across species suggests that larger larvae will have substantially greater success in avoiding predation and are likely to do much better than smaller larvae under conditions of high predator density. Increasing escape capabilities with increasing body size have been commonly observed for larval fishes and amphibians (Batty et al 1993, Williams et al 1996, Fuiman et al 1999, Wesp & Gibb 2003, Eidietis 2005. We did not observe a correlation between larval size and startle performance within species, but this was likely due to the relatively narrow size range within individual species (CV ranged from 2.9 to 3.3% within a species, but was 6.0% for the means of each of the 5 species).…”
Section: Startle Performancecontrasting
confidence: 47%
“…This size-specific predation is observed in part because faster-growing tadpoles quickly become too large for the gape size of certain predators [25,31]. Moreover, weight is generally correlated with swimming speed [32,33], so, although no differences in swimming speed among treatments were found in this study because we controlled for size, fluoxetine may indirectly impact swimming speed by decreasing larval size. Therefore, exposed tadpoles may be less capable of escaping predation because of decreased swimming speed caused by retarded development.…”
Section: Discussionmentioning
confidence: 65%